Advancing climate-smart education in Africa: AICCRA-WASCAL-RUFORUM partnership mainstreams climate-smart agriculture and climate information services in African education systems - Segnon, Alcade (Bioversity International and the International Center for Tropical Agriculture, 2024)
Thanks to AICCRA partnership and engagement, WASCAL and RUFORUM have developed new course modules on climate-smart agriculture and climate information services, informed by CGIAR science. Over 1,500 university lecturers and staff — of which 30% women — from 37 African countries have benefited from capacity development training on the climate course modules. A new master’s degree specialization has been created at the Felix Houphouet Boigny University in Cote d’Ivoire using the climate modules to generate new expertise to transform African agriculture and food systems.